Hyaluronan abrogates imatinib-induced senescence in chronic myeloid leukemia cell lines - Lompardía, Silvina Laura (2019)
Hyaluronan (HA) is the main glycosaminoglycan of the extracellular matrix. CD44 is the most important HA receptor, and both have been associated with poor prognosis in cancer. Chronic myeloid leukemia (CML) is characterized by the presence of a constitutively activated tyrosine kinase (Breakpoint Cluster Region - Abelson murine leukemia viral oncogene homolog1, BCR-ABL). It is mainly treated with BCR-ABL inhibitors, such as imatinib. However, the selection of resistant cells leads to treatment failure. The aim of this work was to determine the capacity of HA (high molecular weight) to counteract the effect of imatinib in human CML cell lines (K562 and Kv562). We demonstrated that imatinib decreased HA levels and the surface expression of CD44 in both cell lines. Furthermore, HA abrogated the anti-proliferative and pro-senescent effect of Imatinib without modifying the imatinib-induced apoptosis. Moreover, the inhibition of HA synthesis with 4-methylumbelliferone enhanced the anti-proliferative effect of imatinib. These results suggest that Imatinib-induced senescence would depend on the reduction in HA levels, describing, for the first time, the role of HA in the development of resistance to imatinib. These findings show that low levels of HA are crucial for an effective therapy with imatinib in CML.